MAKE YOURSELF CLEAR: EXPERIENCE FOR SUBMITTED PATIENTS TO MECHANICAL VENTILATION WITHOUT SEDATION SIDE EFFECTS - Henao Castaño, Ángela Maria (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The mechanical ventilation mechanism is a support method used to safeguard the life of people in a critical state. Traditionally, it has been used in patients under the effects of continuous sedation, which implies a total abstraction of their current situation for the patients; such scenarios afford the patients a traumatic one to wake up, broadly informed in the literature, for the adverse effects of the sedative medications, like the psychological implications that it can cause independent of quality of care. Objective: to describe the different communication forms used for patients whose experience in an intensive critical care unit has involved the mechanical ventilation without continues sedation effects. Methodology: the investigation was carried out with phenomenological focus during 2006 and had the participation of seven men and two women with ages between 24 and 75 years of age. The technique of information gathering was the in-depth interview. Results: The description of each experience allowed understanding of the human being critically sick with an artificial air way as living medium, requesting active ways to be made understood. Conclusion: it demonstrated the importance for the patient to be treated as an active subject by means of the communication with the health personnel and relatives. Many non verbal tools were employed and their contribution brought upon a positive perception of the experience.